1997
DOI: 10.1161/01.cir.95.6.1425
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Anti-Phospholipid Antibodies and Endothelial Perturbation in Systemic Lupus Erythematosus Patients With Ongoing Prothrombotic State

Abstract: This study shows that in SLE patients, aPL positivity is associated with an ongoing prothrombotic state only in the presence of endothelial perturbation. Our findings also suggest that aPLs and TNF-alpha might cooperate in inducing endothelial perturbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 37 publications
(11 reference statements)
4
48
0
2
Order By: Relevance
“…The signal peptide [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] is underlined in the figure. The protein was further subjected to PROSITE and ASC analyses (see "Bioinformatic analysis"), which indicated that the following cysteine residues are likely to be involved in disulfide bond formation and to be responsible for the Sushi domain secondary structure: C23-C66, C51-C79, C84-C124, C110-C137, C142-C188, C174-C200, C205-C248, and C234-C260.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal peptide [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] is underlined in the figure. The protein was further subjected to PROSITE and ASC analyses (see "Bioinformatic analysis"), which indicated that the following cysteine residues are likely to be involved in disulfide bond formation and to be responsible for the Sushi domain secondary structure: C23-C66, C51-C79, C84-C124, C110-C137, C142-C188, C174-C200, C205-C248, and C234-C260.…”
Section: Resultsmentioning
confidence: 99%
“…3 This glycoprotein is also the most common target for antiphospholipid antibodies frequently associated with vascular cell dysfunction, 4 thrombotic events, and pro-atherogenic mechanisms. [5][6][7][8] In chronic disorders related to endothelial cell dysfunction, such as systemic lupus erythematosus, antiphospholipid antibody syndrome (APS), and atherosclerosis, ␤ 2 GPI plays a role as a target antigen for an immune-mediated attack, possibly influencing the progression of disease. 9-13 ␤ 2 GPI stimulates a vigorous adaptive humoral response, but also a cellular immune response.…”
Section: Introductionmentioning
confidence: 99%
“…42 The conversion of a normal nonthrombotic state into a prothrombotic state may be the primary pathophysiological event in APS. In a recent study, Ferro et al 44 illustrated that in patients with systemic lupus erythematosus (SLE), aPL positivity is associated with an ongoing prothrombotic state only in the presence of EC perturbation, which can be measured by elevated levels of tissue plasminogen activator and von Willebrand factor. More recently, Martini and colleagues, 45 in a series of 22 SLE patients and 20 healthy individuals, evaluated the presence of aCL, LA, and/or aCL compared with SLE patients without LA and/or aCL and with controls.…”
Section: Discussionmentioning
confidence: 99%
“…Patient eligibility criteria included an established diagnosis of SLE and 1 of the following 5 features: World Health Organization class III or class IV glomerulonephritis (7), uncontrolled with treatment according to the National Institutes of Health short-course CYC protocol (8); parenchymal disease of the heart or lung with biopsy-proven vasculitis, uncontrolled with IV CYC; cerebritis or transverse myelitis, uncontrolled with IV CYC; profound, refractory autoimmune cytopenias; or catastrophic antiphospholipid syndrome (9)(10)(11)(12).…”
Section: Methodsmentioning
confidence: 99%